Fabrication and Evaluation of the Photocatalytic, Antibacterial Activity of Ag–TiO\(_2\) Thin Film - Ton, Nu Quynh Trang; Le, Thi Ngoc Tu; Nguyen, Dang Trai; Vu, Thi Hanh Thu (Communications in Physics, 2017)
Ag–TiO2 thin film was fabricated by DC magnetron sputtering and photoreduction methods. Characteristics of the film such as surface area, crystal structure, and chemical composition were investigated by using scanning electron microscope (SEM), X–ray diffractometry (XRD) and UV–vis spectra. The photocatalytic activity of Ag–TiO2 thin film was determined by the degradation of methylene blue (MB) solution under various irradiation conditions. The antibacterial property of Ag–TiO2 thin film was conducted in E. coli bacteria. Results showed that the photocatalytic and antibacterial property of Ag–TiO2 thin film are better than those of pure TiO2 thin film in the visible region. Ag–TiO2 thin film shows a great potential application in the antibacterial and environment field.